Crop Residue Burning in Northern India: Increasing Threat to Greater India. Issue 13 (10th July 2018) - Sarkar, S.; Singh, R. P.; Chauhan, A.
Abstract: Crop residue burning (CRB) is a recurring problem, during October–November, in the northwestern regions (Punjab, Haryana, and western Uttar Pradesh) of India. The emissions from the CRB source regions spread in all directions through long‐range transport mechanisms, depending upon the meteorological conditions. In recent years, numerous studies have been carried out dealing with the impact of CRB on the air quality of Delhi and surrounding areas, especially in the Indo‐Gangetic Basin (also referred to as Indo‐Gangetic Plain). In this paper, we present detailed analysis using both satellite‐ and ground‐based sources, which show an increasing impact of CRB over the eastern parts of the Indo‐Gangetic Basin and also over parts of central and southern India. The increasing trends of finer black carbon particles and greenhouse gases have accelerated since the year 2010 onward, which is confirmed by the observation of different wavelength dependent aerosol properties. Our study shows an increased risk to ambient air quality and an increased spatiotemporal extent of pollutants in recent years, from CRB, which could be a severe health threat to the population of these regions. Plain Language Summary: This paper shows from multiple evidence increasing effects of crop residue burning on the rest of India. This is the first work of its kind that treats this issue over rest of India at depth based on data from multiple sources and shows the ever increasing menace of biomass burning to air pollution. Key Points: Analysis from multiple sources proves the greater influence of crop residue burning over rest of India This paper shows an increasing effect of crop residue burning over central and eastern India We demonstrate an increasing impact since the year 2010 with an increase in mechanized harvesting practice